Aluminium nanorings: configuration deformation and structural transformation. Issue 16 (29th January 2021) - Geng, Lin; Li, Qiao-Hong; Wang, San-Tai; Liu, Ya-Jie; Fang, Wei-Hui; Zhang, Jian
Abstract : Present herein is the first time that a fatty acid is employed in the assembly of aluminium wheels. Interestingly, a structural transformation between the diol modified and monohydric alcohol is discovered. Abstract : Present herein is the first example of aluminium nanoring assembly by fatty acids. And the auxiliary alcohol sites can be modified either by monohydric alcohols (AlOC-33 to AlOC-35 ) or diols (AlOC-36 to AlOC-38 ). The monohydric alcohol modified ten-membered aluminium (Al10 ) rings are coplanar, while the diol modified ones possess a saddle-shaped configuration. Interestingly, the diol modified Al10 ring (AlOC-36 ) can convert into a coplanar ring (AlOC-33-B ). AlOC-33-B possesses a similar molecular structure but a different supramolecular structure with AlOC-33 . The structural transformation is confirmed to be a thermodynamically spontaneous process through density-functional theory (DFT) calculations.